Mediation, Remediation, and Commercialization of Indonesian Identity in Sneakers Advertising - Dewi Kartika Sari (Universitas Muhammadiyah Yogyakarta, 2022)
The utilization of Indonesian national identity in fashion products, notably shoes, inspired this research. Retail goods that exhibited an Indonesian identity offered producers a chance to draw in sneakers fans. This research aimed to discuss the mediatization of Indonesian national identity. The three Instagram accounts @exodos57, @bro.do, and @sepatucompass were selected as the study’s subjects. Young Indonesians are currently enamored of sneakers from these brands. Many young individuals also follow their Instagram accounts. The data was to be analyzed using mediation, remediation theory, and commercialization. To investigate the data, a qualitative technique using explanatory research was used. The findings demonstrated that mediation, remediation, and commercialization are three processes that engage with one another. Additionally, it is possible to interpret the utilization of national identity as a response to globalization and the quest for authenticity. The logic of commercialization might be applied to this legitimate research.